China-Brazil Economic Relations: Too Big to Fail? - Powell, Dawn Elizabeth (2012)
This article analyzes Brazil’s economic policy towards China in light of the major influx of Chinese imports and investment into Brazil in the 2000s. In particular, I explore the significance of domestic actors in the Brazilian political debate surrounding the entrada chinesa, and their success in pressuring the government to adopt protectionist policies. These dynamics are exemplified through a detailed case study on Chinese investment in the Brazilian soy industry. In sum, my findings underscore the ways in which Brazil is falling short of capturing the benefits presented by Chinese trade and investment.